Mahi Tahi - Rū Whenua: Tangata Whenua & Kairangahau Pūtaiao. Reflective Learnings on Partnering With Indigenous Māori Communities in Field-Based Scientific Research - Mestel ERH; Smith B; Tapuke K; Illsley-Kemp F; Kaiser L; Connon I; Johnston D; Wilson CJN; Leonard G; Clive MAT; Savage MK (Wiley Periodicals LLC on behalf of American Geophysical Union, 2025)
Between 2018 and 2022, representatives of local Indigenous Māori communities and emergency management worked in partnership with physical and social scientists during the planning, deployment, and management of a temporary seismometer network around Taupō volcano. This deployment formed part of the Eruption or Catastrophe: Learning to Implement Preparedness for future Supervolcano Eruptions (ECLIPSE) project designed to increase understanding of the large caldera volcanoes in the central North Island of Aotearoa New Zealand. Here we critically reflect on this co-production approach to geophysical network deployment and associated volcano research. We identified a central theme of the creating and holding of space for researchers and communities to engage in the activities through adopting a co-production approach, that embeds representatives of local Iwi (tribal groups) Te Arawa and Ngāti Tūwharetoa as key researchers within a broad project team. We worked to ensure we were respecting communities' time, protocols, and decisions; and to exchange knowledge about the research and results with landowners, community leaders, schools, and young people. Time spent kanohi ki te kanohi (face-to-face) built relationships and trust within and outside the research team that have lasted beyond the scope of the ECLIPSE program. We detail our experiences in the hope of demonstrating that this approach to research is a possible and desirable path for future fieldwork-based research.